(untitled) (Journal of Nuclear Technology in Applied Science, 2025)
The efficiency of gamma radiation doses was tested against some biological aspects of the progeny of Galleria mellonella. Male and/or female full-grown pupae were irradiated with 40, 100, 160, 200 and 260Gy. The results showed that the fecundity, % egg hatchability, % pupation and adult emergence were negatively correlated with the dose increase. On the other hand, % sterility, egg incubation period and the larval duration were increased significantly (p<0.05) with the increase of doses used. In general, the results indicated that the biological activity of gamma irradiation against G. mellonella larvae was more remarkable when both crossed females and males were irradiated followed by irradiated females crossed with non-irradiated males.